Label-Free electrochemical capacitive biological sensors for molecular diagnostics - Lucas Garrote, Beatriz [UNESP] (2022)
The recent advances in biomedicine and technology have risen the popularization of molecular diagnosis which refers to the use of molecular techniques, such as polymerase chain reaction (PCR) or enzyme-linked immunosorbent assay (ELISA), to analyze biological markers (e.g., proteins, DNA or RNA). Both PCR and ELISA have been improved over the years with a broad range of applications. Nonetheless, both techniques have limitations that complicate their access in developing countries or their application in the field, since both need costly and high-size equipment with a stable source of power, costly reagents, and additional steps, which turn them into time-consuming assays, and high-qualified personnel to run the assays. REASSURED Point-of-care (POC or bedside testing) molecular diagnosis devices appear to overcome those limitations due to the facility to use handheld devices to medically examine a patient during a consultation where doctors and patients are no longer required to wait for lab results to make an appropriate diagnosis. Therefore, POC devices have the potential to become the primary care tool to diagnosis diseases in which the detection time is crucial to initiate the treatment, as is the case in non-communicable diseases (NCDs), and to avoid the spread of infection agents, as it is the case in infectious diseases, reducing the probability of outbreak and multiple deceases. POC molecular diagnosis devices are popularly known as biosensors which are constituted by three elements: receptor, transducer, and output system. Within those, transducer is the main element, since it is responsible to convert the biological/chemical signal of the analyte-receptor interaction into an electrical signal readable by the output system. The recognition of the analyte by the transducer can be directly (i.e., label-free) on only one-step without additional reagents (reagentless) by the variation of an inherent property of the transducer; or indirectly (i.e., label-based) by using additional steps for analyte labeling or additional labeled-molecules. This requirement increases the duration, the cost and the difficult of handling of the assay, so label-free and reagentless methodologies are more appropriate for POC devices. Those requirements are accomplished by using transducers based on electrochemical capacitance which also offers high-sensitivity and the possibility of miniaturization. Electrochemical capacitive transducers are composed by a redox-active nanostructure immobilized on the electrode surface with discrete energy levels. Those transducers use impedance-derived capacitance spectroscopy as electrochemical technique derived from EIS measurements that measures the electrochemical capacitance (C_μ) of those electroactive nanostructures. C_μ is an intrinsic characteristic of those electroactive nanostructures with thickness < 5nm, related to the energy storage and density-of-states (DOS) of the interface. C_μ biosensors are modelled by the quantum rate theory which resolves the quantum dynamics of the electron transfer (ET) in diffusionless electrochemical reactions, such as one of the electroactive interfaces, given by k=G/C_μ, where k is the electron transfer rate and G is the quantum conductance which measures the charge transport within the electrode and the electroactive interface. This theory demonstrated that in an ideal electron transfer situation, G=G_0, where G_0=g_s e^2/h ~ 77.5 μS is the quantum of conductance. Moreover, it demonstrated that C_μ is a consequence of the series combination of an electrostatic (C_e) and quantum (C_q) capacitances, such as 1/C_μ=(1/C_e)+(1/C_q), where C_e arises from the charge separation (l) due to the solvation of the electroactive switches and C_q emerges from the occupancy of the energy levels within the charge transfer with the electrode through the backbone of the electroactive molecule (L). In most of the quantum C_μ interfaces, l≪L, so C_e≫C_q, 1/C_e is close to zero and C_μ~C_q. According to those approximations, k=G_0/C_q, demonstrating that electroactive interfaces operate in a purely quantum regime, turning them in high-sensitive transducers for biosensing applications. The versatility and high-sensitivity of the C_q transducers convert them into promising tool for the development of analytical assays in a vast range of applications qualitative or quantitative. In this Ph.D. project we proposed the use of electrochemical capacitance transducers to develop novel biosensing assays for the diagnosis of relevant diseases: SARS-CoV-2 infection by the detection of spike protein (SP) and nucleocapsid protein (NP) in nasopharyngeal/oropharyngeal samples; Dengue virus infection by the quantification of NS1 protein in serum samples; and Alzheimer’s disease (AD) by the quantification of ptau-181 and ADAM10 proteins in human serum samples. SARS-CoV-2 is the novel circulating member of the family Coronaviridae that rapidly spread worldwide and became a global health threat. The development of biosensors became a priority until the development of the vaccines. In this doctoral thesis, the SARS-CoV-2 assay developed detected the presence of the viral proteins S and N in nasopharyngeal/oropharyngeal human samples with 77% of specificity and 80% of sensitivity, higher than the overall commercial rapid assays. Dengue virus also constituted a health threat in some tropical countries, such as Brazil. Efficient POC devices could provide rapid detection of the infection and monitorization of the progression of the disease to more severe haemorrhagic dengue. Thus, in this project we developed a miniaturized and high-sensitive Dengue virus assay for the quantification of the viral protein NS1. A novel amplifier signal methodology was coupled to the assay which increased up to 1000 times its sensitivity, enabling the detection of the virus since the biggening of the infection. Moreover, in this doctoral thesis, C_q transducers were applied to the first-time label-free quantification of two AD serum biomarkers, ADAM10 and ptau-181. Two ADAM10 assay were developed by using two antibodies that recognized a distinct ADAM10 isoforms. The analytical features of each assay were resolved by measurements on the C_q transducer which enable the determination of the association constant (K_a), limit-of-detection (LOD), limit-of-quantification (LOQ). Both assays demonstrated similar K_a and LODs and LOQs in the nanogram per millilitre range. Also, the specificity of each assay was analysed by the quantification of the protein in serum samples from AD patients and healthy individuals. In the case of the ptau-181 assay, the concentration range in human serum samples was picogram per milliltre, so three different C_q transducers based on a redox peptide self-assembled monolayer (SAM), the redox peptide SAM coupled to the amplifier signal methodology and a CdTe quantum dot ensemble, were analysed in terms of LOD and LOQ to evaluate which of them would be suitable for the application. The sensitiveness of the rPep SAM was not enough to quantify the protein in such concentration range, while the alternative with the amplifier signal and the QD-based transducers were suitable for the application. In summary, in this doctoral thesis it was demonstrated the potential of the electrochemical capacitance technique for the development of transducers for POC devices. The versatility of the technique enables a vast range of applications which diverse analytical features requirement. Accordingly, the objectives proposed in the beginning of this project were successfully achieved and new prospect for future research have been created.